Pengaruh Pemberian Perasan Labu Siam (Sechium Edule) terhadap Penurunan Tekanan Darah pada Penderita Hipertensi - Sri Jumiati; Miftahul Rauzah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Hypertension can lead to various complications, including stroke, heart attack, the accumulation of fatty plaques and calcium deposits in blood vessel walls, rupture of cerebral capillaries, damage to blood vessels, renal blood vessel rupture, chronic kidney failure, and, in severe cases, hypertensive encephalopathy, which may result in decreased consciousness or even coma. Therefore, non-pharmacological management is needed to alleviate symptoms in patients with hypertension, one of which is the administration of chayote juice (Sechium edule). This study aimed to determine the effect of chayote juice administration on reducing blood pressure in patients with hypertension. The study employed a case study method involving four patients diagnosed with hypertension. The intervention consisted of administering chayote juice for four consecutive days. On the fourth day of evaluation, the patients' blood pressure decreased to 130/80 mmHg. The findings demonstrated that chayote juice was effective in lowering blood pressure from 160/100 mmHg to 130/80 mmHg after four days of administration. Therefore, patients with hypertension may utilize chayote juice as a non-pharmacological therapy to help reduce high blood pressure when consumed regularly.